Commercial sexual trafficking of males: A pilot training with law enforcement - Kenny, Maureen C. (Criminal justice studies, 2023)
Law enforcement agents are often the first professionals to come into contact with victims of commercial sexual trafficking (CST). While they likely have encountered female victims of CST, they may need increased understanding of the identification of male victims. This study evaluated the effectiveness of a training program aimed to increase awareness of male victims of CST among law enforcement professionals. Participants’ (N = 132) knowledge level was examined prior to the training and immediately thereafter and results showed that pretest knowledge scores were low. The majority of participants (77%) did not have prior training in CST in males and there was a significant gain in knowledge from pre to posttest. None of the participants’ demographic variables were significant predictors of pretest or posttest scores. Implications for training law enforcement in male CST are provided.